2000
DOI: 10.1164/ajrccm.161.3.9906006
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Reference Equations for Slow Vital Capacity and Flow–Volume Curve Indexes

Abstract: We derived reference values for slow vital capacity (VC) and flow-volume curve indexes (FVC, FEV(1), and flows) from the 1,185 tracings provided by 1,039 "normal" subjects who participated in one or both cross-sectional surveys of the Po River Delta study in 1980-1982 and in 1988-1991. Definition of "normal" was based on negative answers to questions on respiratory symptoms/diseases or recent infections, current/past tobacco smoking, and work exposure to noxious agents. Reference equations were derived separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
2
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 18 publications
4
47
2
2
Order By: Relevance
“…1 Several authorities have reported the effect of weight on VC. 5,6 The VC decreases with increasing BMI. Obesity reduces lung compliance, 15 and, as a consequence, it decreases VC.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1 Several authorities have reported the effect of weight on VC. 5,6 The VC decreases with increasing BMI. Obesity reduces lung compliance, 15 and, as a consequence, it decreases VC.…”
Section: Discussionmentioning
confidence: 95%
“…4 Obesity can decrease a patient's vital capacity, as reflected in both FVC and SVC measurements. [5][6][7] To our knowledge, however, it is not known whether body mass index (BMI) affects FVC more than SVC. If obesity reduces FVC more than SVC, the FEV 1 /FVC ratio may be artificially low in obese individuals, leading to underdiagnosis of OAD.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently no statistical techniques allowed accurate and continuous description of pulmonary function from childhood to old age. However, with the advent of new techniques, notably the GAMLSS technique [10,[20][21][22][23] it is now possible to summarise pulmonary function across the whole age range. In addition, it allows the lower limit of normal (usually the fifth percentile), which varies appreciably with age [10,15,16,22], to be modelled properly.…”
Section: Lung Function Ph Quanjer Et Almentioning
confidence: 99%
“…6,7 The initial increase is thought to be a 'muscularity effect', while the decrease with high BMI values may be due to an 'obesity effect' on the mobility of the thorax. 7 Pistelli et al 6 reported that in a male non-smoking healthy Italian population, the value at which the direction of the association between lung function and BMI changed was 25.7 kg/m 2 . Our results are in agreement with these findings, showing a strong detrimental effect of adult BMI among those who are overweight or obese, and no effect among those normal and underweight.…”
Section: Controlsmentioning
confidence: 99%
“…A few studies have reported that pulmonary function increased with increasing BMI within lower BMI values and then decreased with further increases. 6,7 Moreover, weight gain has been associated with the longitudinal decline of both FEV 1 and forced vital capacity (FVC) in general population samples. 8,9 Some studies have explored the relationship between BMI and lung function in childhood; 10 however, to our knowledge, the association between BMI in childhood and adult lung function has not been investigated.…”
Section: Introductionmentioning
confidence: 99%